DAMPAK DARI SISTEM KERJA HYBRID DAN WORK FROM HOME (WFH) TERHADAP KEPUASAN DAN MOTIVASI KERJA APARATUR SIPIL NEGARA DI SEKRETARIAT DAERAH KABUPATEN WONOGIRI - Okthavilia Rizky Amanda Putri; Achmad Choerudin; Retnoning Ambarwati (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the impact of hybrid work systems and Work From Home (WFH) on the job satisfaction and work motivation of Civil Servants (ASN) at the Regional Secretariat of Wonogiri Regency. The background of this research stems from the transformation of the government bureaucratic work system, which is increasingly moving toward flexible work patterns in line with the development of information technology and digitalization of public services. This study employs a quantitative approach with multiple linear regression analysis. The research population consists of all ASN at the Regional Secretariat of Wonogiri Regency, with a sample of 65 respondents selected using purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results show that: (1) the hybrid work system has a positive and significant effect on ASN job satisfaction with a t-count of 5.481 and significance of 0.000; (2) Work From Home (WFH) does not significantly affect ASN work motivation with a t-count of 1.123 and significance of 0.266; (3) simultaneously, the hybrid work system and WFH significantly affect job satisfaction (F-count 70.395, sig. 0.000) and ASN work motivation (F-count 18.063, sig. 0.000). The coefficient of determination shows that the hybrid work system and WFH can explain the variation in job satisfaction by 69.4% and work motivation by 36.8%. These findings indicate that a structured hybrid work system is more effective in increasing ASN job satisfaction and work motivation compared to WFH implemented in isolation. This research provides practical implications that the implementation of flexible work systems needs to be integrated with broader HR management policies to achieve optimal results.